DNA metabarcoding of gut contents reveals key habitat and seasonal drivers of trophic networks involving generalist predators in agricultural landscapes. Issue 12 (24th September 2022) - Saqib, Hafiz Sohaib Ahmed; Sun, Linyang; Pozsgai, Gabor; Liang, Pingping; You, Minsheng; Gurr, Geoff M.; You, Shijun
Abstract: BACKGROUND: Understanding the networks of trophic interactions into which generalist predators are embedded is key to assessing their ecological role of in trophic networks and the biological control services they provide. The advent of affordable DNA metabarcoding approaches greatly facilitates quantitative understanding of trophic networks and their response to environmental drivers. Here, we examine how key environmental gradients interact to shape predation by Lycosidae in highly dynamic vegetable growing systems in China. RESULTS: For the sampled Lycosidae, crop identity, pesticide use and seasons shape the abundance of prey detected in spider guts. For the taxonomic richness of prey, local‐ and landscape‐scale factors gradients were more influential. Multivariate ordinations confirm that these crop‐abundant spiders dynamically adjust their diet to reflect environmental constraints and seasonal availability to prey. CONCLUSION: Plasticity in diet composition is likely to account for the persistence of spiders in relatively ephemeral brassica crops. Our findings provide further insights into the optimization of habitat management for predator‐based biological control practices. © 2022 Society of Chemical Industry. Abstract : Crop‐abundant spiders are found to adapt their foraging behavior in response to environmental constraints and seasonal availability of prey. The plasticity in the diet composition indicated that spiders are extremely adaptable to changing environments, implying their significance as biological control agents in agro‐ecosystems, particularly those with highly dynamic growing systems.